2015
DOI: 10.4238/2015.june.11.9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of virus load in supernatant of primary CEK cell culture infected with different generations of avian infectious bronchitis virus strains Sczy3 as revealed by real-time reverse transcription-polymerase chain reaction

Abstract: ABSTRACT. Infectious bronchitis virus (IBV) can multiply effectively in chick embryo kidney (CEK) cells after adapting to the chick embryo. To investigate the dynamic changes in IBV load in the supernatant of primary CEK cells, we developed an SYBR Green I-based real-time polymerase chain reaction assay to quantify nucleic copy numbers of the IBV-Sczy3 strain. The 20, 54, and 87th generations of CEK-adapted IBV-Sczy3 strains were used to infect CEK cells, and then nucleic copy numbers in the samples of superna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Previous study documented that epithelial cell was the primary site of replication of avian NIBV, the increased level of virion in CK cells lead to destructions of the cellular structure and composition, which caused the cell membranes damage (Sun et al, 2014). Interestingly, the characteristic syncytia and plaque was observed in CEK cells after transfected by IBV Sczy3 virus (Wei et al, 2015) and intracytoplasmic brownish colouration was observed by immunoperoxidase in primary chick embryo chorioallontoic membrane cells after infection by IBV (Ghetas et al, 2015). The results are similar to our study: post infected by NIBV, the cytopathic effect was found and the cell viability of CK cells was significant reduced.…”
Section: Discussionsupporting
confidence: 90%
“…Previous study documented that epithelial cell was the primary site of replication of avian NIBV, the increased level of virion in CK cells lead to destructions of the cellular structure and composition, which caused the cell membranes damage (Sun et al, 2014). Interestingly, the characteristic syncytia and plaque was observed in CEK cells after transfected by IBV Sczy3 virus (Wei et al, 2015) and intracytoplasmic brownish colouration was observed by immunoperoxidase in primary chick embryo chorioallontoic membrane cells after infection by IBV (Ghetas et al, 2015). The results are similar to our study: post infected by NIBV, the cytopathic effect was found and the cell viability of CK cells was significant reduced.…”
Section: Discussionsupporting
confidence: 90%
“…The amplicons were then inserted into pMD-19T cloning vector (Takara Bio-Inc, Dalian, China) and transformed into Escherichia coli TOP10 competent cells (Takara Bio-Inc, Dalian, China). The recombinant plasmid DNA was extracted, and its copy numbers were calculated according to a previous report [29].…”
Section: Standard Plasmidmentioning
confidence: 99%